Noble‐Noble Strong Union: Gold at Its Best to Make a Bond with a Noble Gas Atom - Pan, Sudip (ChemistryOpen, 2019)
This Review presents the current status of the noble gas (Ng)‐noble metal chemistry, which began in 1977 with the detection of AuNe(+) through mass spectroscopy and then grew from 2000 onwards; currently, the field is in a somewhat matured state. On one side, modern quantum chemistry is very effective in providing important insights into the structure, stability, and barrier for the decomposition of Ng compounds and, as a result, a plethora of viable Ng compounds have been predicted. On the other hand. experimental achievement also goes beyond microscopic detection and characterization through spectroscopic techniques and crystal structures at ambient temperature; for example, (AuXe(4))(2+)(Sb(2)F(11) (−))(2) have also been obtained. The bonding between two noble elements of the periodic table can even reach the covalent limit. The relativistic effect makes gold a very special candidate to form a strong bond with Ng in comparison to copper and silver. Insertion compounds, which are metastable in nature, depending on their kinetic stability, display an even more fascinating bonding situation. The degree of covalency in Ng–M (M=noble metal) bonds of insertion compounds is far larger than that in non‐insertion compounds. In fact, in MNgCN (M=Cu, Ag, Au) molecules, the M−Ng and Ng−C bonds might be represented as classical 2c–2e σ bonds. Therefore, noble metals, particularly gold, provide the opportunity for experimental chemists to obtain sufficiently stable complexes with Ng at room temperature in order to characterize them by using experimental techniques and, with the intriguing bonding situation, to explore them with various computational tools from a theoretical perspective. This field is relatively young and, in the coming years, a lot of advancement is expected experimentally as well as theoretically.